2021
DOI: 10.1002/ange.202101248
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosynthesis of Higher‐Order Cocrystals: Tuning Order, Functionality and Size in Cocrystal Design**

Abstract: The ability to rationally design and predictably construct crystalline solids has been the hallmark of crystal engineering research. To date,n umerous examples of multicomponent crystals comprising organic molecules have been reported. However,t he crystal engineering of cocrystals comprising both organic and inorganic chemical units is still poorly understood and mostly unexplored. Here,w er eport anew diverse set of higher-order cocrystals (HOCs) based on the structurally versatile-yet largely unexplored-pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 75 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…32,34,44 In addition, these species have been shown to effectively bind to small molecules (e.g., acetone, DMSO and DMF), and be versatile building blocks for the engineering for high-order ternary and quaternary multicomponent cocrystals, which further broadens the scope of their applications in supramolecular applications and crystal engineering. 28,45 Common strategies for improving the HB donor ability of urea and thioureas for their use as building block in both supramolecular chemistry and molecular machines are to increase (i) the complexity (i.e., adding extra HB functionalities, electron withdrawing groups, etc.) of the substituents (Approach 1) [46][47][48] or (ii) the number of repeating units of urea/thiourea crafted within the molecular backbone (Approach 2).…”
Section: Broader Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…32,34,44 In addition, these species have been shown to effectively bind to small molecules (e.g., acetone, DMSO and DMF), and be versatile building blocks for the engineering for high-order ternary and quaternary multicomponent cocrystals, which further broadens the scope of their applications in supramolecular applications and crystal engineering. 28,45 Common strategies for improving the HB donor ability of urea and thioureas for their use as building block in both supramolecular chemistry and molecular machines are to increase (i) the complexity (i.e., adding extra HB functionalities, electron withdrawing groups, etc.) of the substituents (Approach 1) [46][47][48] or (ii) the number of repeating units of urea/thiourea crafted within the molecular backbone (Approach 2).…”
Section: Broader Contextmentioning
confidence: 99%
“…Past reports on monomeric cyclodiphosphazane receptors have shown that strong HB guest, such as halide anions, favour the exo,exo conformation, 45,71 which enables these species to act as R 2 1(8) HB donors. 29,34,44 This preference for the exo,exo (over the exo,endo) in the presence of halide HB acceptors, has also been recently highlighted during the formation of high-order multicomponent cocrystals based on monomeric P V 2N2 building blocks 45. The presence of an additional P V 2N2 provide 2 and 3 with an additional degree of freedom (i.e., OFF vs ON conformations), and could potentially provide a superior performance towards anion binding and sensing if selectively switched ON.…”
Section: Synthesis Of Acyclic Dimeric-p V 2n2 Molecular Switchesmentioning
confidence: 99%
“…This review will summarize recent advancements in the usage of organic cocrystals for spin applications, rather than the preparation methods of organic cocrystals since several excellent reviews have been documented previously [4,20] . Besides the magnetic and multiferroic properties in binary/ternary cocrystals, other spin phenomena (spin multiplicity, mechanoresponsive spin, chiral orbit and spin‐crossover) and the mobility of spin transport are also summarized and discussed.…”
Section: Introductionmentioning
confidence: 99%
“…2 Among them, the ionic cocrystals of organic salts crystallising together with one or more neutral molecules of acid or base or with one or more neutral components are known in the literature. [5][6][7][8][9][10] However, beyond their structural features, their properties have not been explored in detail. In general, pK a differences among partner conjugate acid-base molecules play a decisive role in their crystallisation in a particular form.…”
Section: Introductionmentioning
confidence: 99%